Alternative Approaches to Innovation Project Portfolio Governance - Tuominen, Siiri (Sage, 2025)
The governance of projects is often treated operationally, as project portfolio management. Project portfolio governance is more strategic and continuous than project portfolio management, but its various approaches are weakly understood. This study explores project portfolio governance in innovative companies. The resulting framework characterizes governance approaches in terms of the authority given to portfolio actors and the rhythm of using governance practices. Differences among the delegated, regulated, and consultative governance approaches appear to stem from the industry clock speed, innovation portfolio type, and organizational context. This study differentiates project portfolio governance approaches as part of organizational project management governance.